2011
DOI: 10.1112/s0010437x11007068
|View full text |Cite
|
Sign up to set email alerts
|

Kähler groups, real hyperbolic spaces and the Cremona group. With an appendix by Serge Cantat

Abstract: Generalizing a classical theorem of Carlson and Toledo, we prove that any Zariski dense isometric action of a Kähler group on the real hyperbolic space of dimension at least three factors through a homomorphism onto a cocompact discrete subgroup of PSL 2 (R). We also study actions of Kähler groups on infinite-dimensional real hyperbolic spaces, describe some exotic actions of PSL 2 (R) on these spaces, and give an application to the study of the Cremona group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 47 publications
2
35
0
2
Order By: Relevance
“…Manin [Man74] showed that the Cremona group acts faithfully by isometries on an infinite-dimensional hyperbolic space, known as the Picard-Manin space, which is not separable. However, any finite-generated subgroup preserves a totally geodesic closed subspace, which is separable, see for example Delzant and Py [DP12].…”
Section: Examples and Discussionmentioning
confidence: 99%
“…Manin [Man74] showed that the Cremona group acts faithfully by isometries on an infinite-dimensional hyperbolic space, known as the Picard-Manin space, which is not separable. However, any finite-generated subgroup preserves a totally geodesic closed subspace, which is separable, see for example Delzant and Py [DP12].…”
Section: Examples and Discussionmentioning
confidence: 99%
“…5.1]) for Banach vector bundles (with infinite-dimensional base). Results in this direction were recently obtained in [15] and [35].…”
Section: Classification Of Reproducing Kernelsmentioning
confidence: 81%
“…It is a standard fact that the most difficult part to obtain smoothness of weak harmonic maps is the first regularity step, which is the continuity of the harmonic map (see for example [Jos11,8.4]). In our situation, we already know that the harmonic map is Lipschitz and we can easily adapt the argument given in [DP12], where the target is the infinite dimensional hyperbolic space. Proof.…”
Section: Smoothnessmentioning
confidence: 99%